Penggunaan Metode Snow Ball Throwing untuk Meningkatkan Hasil Belajar Matematika Soal Cerita pada Siswa SD - Sepni Yanti (Peneliti.net, 2020)
This research is a classroom action research that aims to describe the results of learning mathematics in story problems using the Cooperative Model Type Snowball Throwing. The second objective is to find out whether the Snowball Throwing type of cooperative learning model is effectively used in learning mathematics in the subject matter. The output that will be generated from this research is the application of fun learning alternatives so that it can improve student mathematics learning outcomes in the Snowball Throwing method. The subjects were 34 students in grade IV in elementary school. The results showed that the application of the Snowball Throwing cooperative learning model was more effective and could improve student learning outcomes.